1993
DOI: 10.1136/bmj.307.6915.1312
|View full text |Cite
|
Sign up to set email alerts
|

Bed sharing, smoking, and alcohol in the sudden infant death syndrome. New Zealand Cot Death Study Group.

Abstract: Objectives-To investigate why sharing the bed with an infant is a not consistent risk factor for the sudden infant death syndrome in ethnic subgroups in New Zealand and to see if the risk of sudden infant death associated with this practice is related to other factors, particularly maternal smoking and alcohol consumption.Design-Nationwide case-control study. 0-44 to 2-18). Neither maternal alcohol consumption nor the thermal resistance of the infant's clothing and bedding interacted with bed sharing to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
171
4
4

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(185 citation statements)
references
References 23 publications
6
171
4
4
Order By: Relevance
“…The increased risk for SIDS among bedsharing infants including AA infants is well documented. 8,12,13 Recent findings confirm that bedsharing is a risk factor for SIDS in US urban, predominately AA populations. 5,16 A number of studies have reported a positive interaction between maternal smoking and bedsharing.…”
Section: Discussionsupporting
confidence: 57%
“…The increased risk for SIDS among bedsharing infants including AA infants is well documented. 8,12,13 Recent findings confirm that bedsharing is a risk factor for SIDS in US urban, predominately AA populations. 5,16 A number of studies have reported a positive interaction between maternal smoking and bedsharing.…”
Section: Discussionsupporting
confidence: 57%
“…In fact, in a recent epidemiologic study from New Zealand, bed sharing (defined as bed sharing with anyone) was found to increase significantly the risk for SIDS when practiced in association with maternal smoking. 57 A subsequent epidemiologic study in southern California 58 failed to find increased risk for SIDS associated with similarly defined bed sharing when passive smoking was controlled for in the analysis; and a recent epidemiologic study in the United Kingdom 59 found that bed sharing with a parent(s) was associated with increased risk only in conjunction with parental smoking. It is also noteworthy that the New Zealand study found that room sharing (as opposed to bed sharing) with one or more adults conferred significant protection against SIDS, whereas room sharing with children did not.…”
Section: Discussionmentioning
confidence: 99%
“…(4,5) As the rate of prone positioning has declined, other previously unrecognized risk factors for sudden unexplained infant death have emerged in recent epidemiologic studies. Despite the fact that bedsharing between an infant and adult facilitates breastfeeding and enhances parent-infant interactions, (6,7) this sleeping arrangement has been identified in epidemiologic studies as being hazardous in certain situations, particularly when one or both parents are smokers, (8)(9)(10)(11)(12) on excessively soft surfaces, such as waterbeds, sofas, and armchairs, (9,10,(13)(14)(15) or when the infant is less than 2-3 months of age. (9,12,(14)(15)(16)(17) In addition, there is an increased risk for sudden unexpected infant death when there are multiple bedsharers (13) and when bedsharing occurs for the entire night.…”
mentioning
confidence: 99%
“…(9,12,(14)(15)(16)(17) In addition, there is an increased risk for sudden unexpected infant death when there are multiple bedsharers (13) and when bedsharing occurs for the entire night. (9,11) The risk for infant death may also be increased when the bedsharer has consumed alcohol or is overtired. (11,16) While it may not be bedsharing itself but the accompanying conditions that are hazardous, bedsharing may increase the risk in certain circumstances for overheating, (18) rebreathing, (19) and exposure to tobacco smoke, (20)all of which are known risk factors for SIDS.…”
mentioning
confidence: 99%
See 1 more Smart Citation